Para onde caminha a ciência politica? - Bizelli, José Luís [UNESP] (My University, 1999)
The purpose of this paper is to analyze the challenges to Political Sciences at the moment when many authors emphasize the usage of democratic paradigm as the only way to the rational building of speech in pluralist societies. At the end of one century of the consolidation of modern liberal thought, both in right and left versions (Wallerstein, 1995), the democracy as research tradition(Ball, 1987) fades away its ethical meaning, based upon equality and freedom, and lacks room for discussions about rules for implementing it. The analytical method seeks to historically rebuild the different levels of modern state-nation upbringing and the consolidation of competitive party democracy in the 20th century, which is the explanation key for the political organizational phenomenon of globalized societies. The result of this analysis opens new perspectives to Political Sciences advance in discussing the nature of democratic paradigm since it needs to face challenges to survive, such as: the fight against the structural violence of our society; the fight against despotism; and the adjustment to the meaning of the word freedom. The facing of the mentioned challenges may open explanation keys that will lead to a change in Political Sciences ways.
Where does political science point to?
Keywords: Democracy; National states; Paradigm changes; Science and politics; Utopian crisis